PELATIHAN DAN PENGUATAN KAPASITAS DALAM MENULIS ARTIKEL ILMIAH DI SEBAGAI KOMPETENSI BERKELANJUTAN DI MGMP MATEMATIKA SMP KABUPATEN TEMANGGUNG - Megita Dwi Pamungkas; Fadhilah Rahmawati; Rifki Hamdani; Muhammad Jibran Al Fauzi; Narisya Diar Permana; Irka Lestari; Muhammad Irvan Ardianto (LPPM Universitas Bina Bangsa, 2024)
Continuous Professional Development includes three things, namely self-development, scientific publications, and innovative work. The problems that occur in partners are still a lack of understanding of mathematics teachers about making scientific articles and still a lack of understanding about the stages of publication of scientific articles in journals through OJS. To facilitate scientific publications of mathematics teachers, Tidar University organizes assistance in writing scientific articles and scientific publications as a means of teacher self-development, especially teachers who are members of the mathematics MGMP of SMP Temanggung Regency. The methods used are socialization (discussion and question and answer), assistance in article preparation, practical exercises in using the open journal system (OJS), and evaluation. At the end of the activity, a survey will be conducted to check the understanding of partners after the activity. The implementation of this Community Partnership Program activity was carried out as many as 2 meetings in the Hall of SMP Negeri 2 Temanggung offline and online using gmeet. Service activities include training, mentoring, and socialization of manuscript submissions to destination journals. The result of the service activities is that junior high school mathematics teachers throughout Temanggung Regency get a good understanding in writing scientific articles and publishing articles in the field of mathematics education